GAMBARAN TINGKAT PENGETAHUAN PENDERITA HIPERTENSI TERKAIT PENYAKIT HIPERTENSI - Soares, Justinho; Soares, Domingos; Seran, Alfonsa Iyoni L.; Lepa, Mariance E.; marni, marni (Akademi Keperawatan Giri Satria Husada Wonogiri, 2021)
Introduction: hypertension is an increase in blood pressure at> 140/90 mmhg. Hypertension is a disease that can kill people secretly or the silent killer. Efforts to treat hypertension and possible complications need to be increased to reduce morbidity and mortality. Aims: to identify the level of knowledge of hypertensive patients on hypertension in the sikumanakupang health center. Method: This MethodÂ use Description design.Â The research instrument used questionnaires and tension meters. The population in this study were 30 people sampling techniques using non probability sampling methods. Results: The description of the level of knowledge based on the score set means Good knowledge consisting of 8 people (26.7%), sufficient knowledge of 12 people (40.0%), and knowledge that is considered less than 10 people.. Conclusion: Through the research results it can be seen that the respondent's level of knowledge is sufficient.